Acquired Digital Fibrokeratoma: A Report of Five Cases and Review of the Literature - Wang X; Zhang D; Lin Q; Niu C; Fan H; Zhang M; Yuan X; Ma W (Dove Medical Press, 2024)
Xing Wang,* Dong Zhang,* Qingxia Lin, Changying Niu, Huiping Fan, Mogen Zhang, Xiangfeng Yuan, Weiyuan Ma Department of Dermatology, Affiliated Hospital of Weifang Medical University, Weifang, Shandong, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiangfeng Yuan; Weiyuan Ma, Department of Dermatology, Affiliated Hospital of Weifang Medical University, Weifang, People's Republic of China, Tel +86-536-3081272, Email nsmcyxf@126.com; fymaweiyuan@wfmc.edu.cnAbstract: Acquired digital fibrokeratoma (ADF) is rare in clinical practice and is easily misdiagnosed. Herein, 5 cases of patients (3 males and 2 females) with ADF are reported. The mean age at onset was 42.6 years, and the mean disease duration was 3 years. Four patients had ADF on the hands, and 1 patient had ADF on the foot. The clinical manifestations were all solitary, skin-colored papules, with a firm texture and smooth surface, protruding from the skin surface. In 3 patients, ADF manifested as columnar protrusions, and in 2 patients, ADF manifested as dome-shaped protrusions. For all 5 patients, the diameters of the lesions were < 1 cm. Clinically, all 5 patients were misdiagnosed (ie, eccrine poroma (EP), common warts, rudimentary polydactyly, pyogenic granuloma (PG), and acral fibroma). All cases of ADF were confirmed by histopathology. The histopathological manifestations of ADF were as follows: finger-like protrusions on the skin surface; collagen fiber bundles running vertically to the epidermis seen in the dermis; and thick red-stained collagen fibers connected with the normal dermal connective tissue below. All 5 patients underwent surgical resection; the distance between the incision margin and the edge of the tumor was 2- 3 mm, and the surgical depth was the deep dermis. No recurrence was observed in more than half a year of follow-up after surgery.Keywords: acquired digital fibrokeratoma, clinical manifestation, histopathology, surgical resection